The Interaction of Job Stress and Social Support: A Strong Inference Investigation - Seers, Anson; McGee, Gail W.; Serey, Timothy T.; Graen, George B. (Academy of Management Journal, 1983)
A comparative examination was made of three alternative hypotheses (buffer, coping, no interaction) predicting job outcomes by job stress and social support. For role ambiguity, little evidence of interaction effects was found. For role conflict, supportive evidence was found for the coping hypothesis, but not the buffer hypothesis, on the work and supervisory satisfaction facets.